Clinical outcomes of carbon ion radiotherapy with concurrent chemotherapy for locally advanced uterine cervical adenocarcinoma in a phase 1/2 clinical trial (Protocol 1001) - Okonogi, Noriyuki; Wakatsuki, Masaru; Kato, Shingo; Karasawa, Kumiko; Kiyohara, Hiroki; Shiba, Shintaro; Kobayashi, Daijiro; Nakano, Takashi; Kamada, Tadashi; Shozu, Makio (Cancer medicine (Malden, MA), 2018)
We conducted a phase 1/2 study to evaluate the efficacy and safety of carbon ion radiotherapy (C‐ion RT) with concurrent chemotherapy for locally advanced uterine cervical adenocarcinoma. Thirty‐three patients were enrolled between April 2010 and March 2014. Treatment consisted of C‐ion RT with concurrent weekly cisplatin at a dose of 40 mg/m2. In the phase 1 component, the total dose was escalated from 68.0 Gy (relative biological effectiveness [RBE]) to 74.4 Gy (RBE) to determine the maximum tolerated dose of C‐ion RT. In the phase 2 component, the efficacy and safety of C‐ion RT with concurrent chemotherapy were evaluated using the dose determined in the phase 1 component. The median follow‐up duration was 30 months. Two patients did not receive chemotherapy because of anemia or leukocytopenia immediately prior to commencing treatment; 31 patients were analyzed. None of the patients developed dose‐limiting toxicities. The recommended dose (RD) was determined to be 74.4 Gy (RBE). In the phase 2 component, two patients developed Grade 3–4 toxicities in the gastrointestinal tract, due to repeated laser coagulation or peritonitis caused by appendicitis. In the patients treated with the RD, the 2‐year local control, progression‐free survival, and overall survival rates were 71%, 56%, and 88%, respectively. C‐ion RT with concurrent weekly cisplatin was well tolerated in patients with locally advanced uterine cervical adenocarcinoma. Our findings support further investigations into the efficacy of this strategy. The efficacy and safety of carbon ion radiotherapy with concurrent chemotherapy was evaluated in patients with locally advanced uterine cervical adenocarcinoma. This strategy was well tolerated in the majority of patients.